Pentingnya Pembelajaran Kontekstual dalam Meningkatkan Pemahaman Konsep Sains pada Siswa SD (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This article aims to explore the importance of contextual learning in improving elementary students' understanding of scientific concepts through a literature review method. The analysis of various sources reveals that the contextual approach enhances students’ learning motivation, active engagement, and conceptual understanding. Learning linked to everyday experiences allows students to construct deeper and more sustainable meanings. Moreover, real-world contexts help develop students' critical thinking and problem-solving skills. Literature studies indicate that integrating contextual approaches into science learning creates a more meaningful and enjoyable learning environment. Previous research also demonstrates improved student achievement in science when contextual learning is applied consistently and systematically. Therefore, it is recommended that teachers design instructional strategies based on local and relevant contexts. In conclusion, contextual learning significantly contributes to enhancing elementary students' understanding of science concepts and deserves to be a primary approach in the basic education curriculum.